Análise estrutural de painéis curvados reforçados sob carregamento de pressão externa uniforme - Marinho, André Luiz Ramalho (2017)
The behavior of reinforced curved panels under uniform external pressure loading is investigated in this study through experimental tests and numerical simulations based on the finite element method. The experimental tests carried out in this investigation cover tensile testings, imperfection measurement and hyperbaric tests. The accuracy of the numerical model is verified in light of experimental results. The results from linear and elastoplastic numerical simulations are presented in the parametric analysis and in the case study. The parametric analysis verifies the influence of geometric parameters on the collapse, while the study case examines the critical pressure of full scale reinforced curved panels. Finally, conclusions based on numerical and experimental results are presented, as well as suggestions for future works.